1994
DOI: 10.1212/wnl.44.1.152
|View full text |Cite
|
Sign up to set email alerts
|

Delayed postanoxic demyelination and arylsulfatase‐A pseudodeficiency

Abstract: We report a patient with delayed postanoxic demyelination who had pseudodeficiency of arylsulfatase A, reducing his enzyme activity to 10 to 30% of normal. This may have implications regarding the pathogenesis of postanoxic demyelination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
25
0
2

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 0 publications
6
25
0
2
Order By: Relevance
“…Moreover, Philpot et al [1997], studying a group of patients with vascular dementia (VaD) and Alzheimer disease (AD), showed that brain DNA from a postmortem sample revealed the ASA pd mutation in 60% of VaD cases and 34% of AD cases; this percentage is higher than previous studies of culturally similar populations and the authors suggested that ASA pd may be a risk factor for dementia. This genetic variant, also found in other sporadic cases with different neurological conditions, such as Lafora disease [Tinuper et al, 1994] or postanoxic demyelination [Weinberger et al, 1994], has never been previously described in WD. Some authors hypothesized that ASA pd may play a role in modulating the severity and the evolution of an associated disease [Weinberger et al, 1994], as suggested for the apo-E allele and Alzheimer disease [Rubinstein et al, 1994], Parkinson disease [Rubinstein et al, 1994], and Creutzfeldt-Jacob disease [Roses et al, 1995].…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Moreover, Philpot et al [1997], studying a group of patients with vascular dementia (VaD) and Alzheimer disease (AD), showed that brain DNA from a postmortem sample revealed the ASA pd mutation in 60% of VaD cases and 34% of AD cases; this percentage is higher than previous studies of culturally similar populations and the authors suggested that ASA pd may be a risk factor for dementia. This genetic variant, also found in other sporadic cases with different neurological conditions, such as Lafora disease [Tinuper et al, 1994] or postanoxic demyelination [Weinberger et al, 1994], has never been previously described in WD. Some authors hypothesized that ASA pd may play a role in modulating the severity and the evolution of an associated disease [Weinberger et al, 1994], as suggested for the apo-E allele and Alzheimer disease [Rubinstein et al, 1994], Parkinson disease [Rubinstein et al, 1994], and Creutzfeldt-Jacob disease [Roses et al, 1995].…”
Section: Discussionsupporting
confidence: 59%
“…This genetic variant, also found in other sporadic cases with different neurological conditions, such as Lafora disease [Tinuper et al, 1994] or postanoxic demyelination [Weinberger et al, 1994], has never been previously described in WD. Some authors hypothesized that ASA pd may play a role in modulating the severity and the evolution of an associated disease [Weinberger et al, 1994], as suggested for the apo-E allele and Alzheimer disease [Rubinstein et al, 1994], Parkinson disease [Rubinstein et al, 1994], and Creutzfeldt-Jacob disease [Roses et al, 1995].…”
Section: Discussionsupporting
confidence: 59%
“…The mechanism underlying the development of this condition is not known, but there is evidence that the hypoxic insult induces widespread demyelination which may be associated with a pseudodeficiency of arylsulphatase A [1,2]. We present two patients, both of whom developed this condition, but in only one of whom was there a pseudodeficiency of this enzyme.…”
mentioning
confidence: 93%
“…It has been associated with a tendency to develop neuropsychiatric disorders As well as neurological findings consistent with atypical MLD [7,8], although others have claimed that it is of no neurological significance [5]. However, it was Weinberger et al [1] and more recently Gottfried et al [2] who first proposed that individuals with a pseudodeficiency state are susceptible to the development of a delayed postanoxic encephalopathy. Although we can further support this observation with one of our cases, it is important to realise that not all cases of postanoxic encephalopathy are associated with reduced levels of arylsulphatase A activity.…”
mentioning
confidence: 99%
“…La patogenia de la leucoencefalopatía hipóxico-hipovolémica no está completamente establecida. Sin embargo, Weinberger y cols, dada la baja frecuencia de la enfermedad, pensaron en enfermedades desmielinzantes familiares y postularon un déficit parcial de arilsulfatasa (ARA) encontrando que esta enzima estaba disminuida en las etapas de recuperación de la hipoxia 6 . En la misma línea Gottfried y colaboradores, en un caso con disminución de arilsulfatasa, observaron aumento de lactato y colina en la espectroscopia, interpretando esta condición como una alteración del metabolismo lipídico y de la mielina 7 .…”
unclassified